Invariant chain cleavage and peptide loading in major histocompatibility complex class II vesicles (The Rockefeller University Press, 1995)
B lymphocytes contain a novel population of endocytic vesicles involved in the transport of newly synthesized major histocompatibility complex (MHC) class II alpha beta chains and alpha beta peptide complexes to the cell surface. We now present evidence that these class II-enriched vesicles (CIIV) are also likely to be a site for the loading of immunogenic peptides onto MHC molecules. We used the serine protease inhibitor leupeptin to accumulate naturally occurring intermediates in the degradation of alpha beta-invariant chain complexes and to slow the intracellular transport of class II molecules. As expected, leupeptin caused an accumulation of Ii chain and class II molecules (I-A(d)) in endosomes and lysosomes. More importantly, however, it enhanced the selective accumulation of a 10-kD invariant chain fragment associated with sodium dodecyl sulfate (SDS)-labile (empty) alpha beta dimers in CIIV. This was followed by the dissociation of the 10-kD fragment, formation of SDS-stable (peptide-loaded) alpha beta dimers, and their subsequent appearance at the cell surface. Thus, CIIV are likely to serve as a specialized site, distinct from endosomes and lysosomes, that hosts the final steps in the dissociation of invariant chain from class II molecules and the loading of antigen-derived peptides onto newly synthesized alpha beta dimers.